Pemberdayaan Guru Menuju Sekolah Adiwiyata Di SD Negeri Sine 1 Sragen - Setiyowati, Lilik Eko, Prof. Dr. Sutama,M.Pd, DR.Sabar Narimo, M.M, M.Pd (2017)
This study has four objectives. (1) Describe the efforts of schools to empower teachers to reach schools Adiwiyata in SD Negeri 1 Sragen Sine. (2) Describe the efforts of teachers to empower themselves to achieve Adiwiyata school. (3) Describe the problems in the school in empowering teachers to achieve school Adiwiyata. (4) Describe the constraints faced by teachers to empower themselves.This type of research is qualitative research design using an ethnographic approach. Data was collected through interviews, observations, and documents. Testing the validity of the data in this study is done by triangulation. Data were analyzed using interactive data analysis. The results of the study, (1) Efforts to empower school teachers in achieving Adiwiyata school is held IHT, training skills, to enable supervision of learning, and build teams Adiwiyata. (2) Efforts teachers empower themselves to achieve Adiwiyata school is how to improve teacher competence independently in preparing the learning, improving skills-based Adiwiyata. (3) Constraints faced by schools in empowering teachers, among others, the implementation of a curriculum that does not comply with the school Adiwiyata, lack of a culture of discipline of teachers in environmental management, there is no budget for the implementation of the empowerment of teachers in achieving Adiwiyata School, and school facilities are lacking ( 4) Constraints faced by teachers in empowering themselves, among others, lack of motivation in learning Adiwiyata based environment, lack of professionalism in managing waste / garbage, less skilled in plant breeding